Effect of 4% titanium tetrafluoride solution on the erosion of permanent and deciduous human enamel: An in situ/ex vivo study - Magalhães, Ana Carolina; Rios, Daniela; Honório, Heitor Marques; Delbem, Alberto Carlos Botazzo [UNESP]; Buzalaf, Marília Afonso Rabelo (FapUNIFESP (SciELO), 2009)
This in situ/ex vivo study assessed the effect of titanium tetrafluoride (TiF4) solution on erosion of permanent (P) and deciduous (d) human enamel. Ten volunteers wore acrylic palatal appliances containing 4 enamel samples, divided into two rows: TiF4 and no - TiF4 (control). Each row contained one deciduous and one permanent enamel sample. During the 1st day, formation of a salivary pellicle was allowed. At the 2 nd day, the 4% TiF4 solution was applied on one row (TiF4), while the other row remained untreated (control). From the 3rd until the 7th day, the samples were subjected to erosion by immersion in a cola drink for 5 min, 4 times/day. Enamel alterations were determined by microhardness testing (%SMHC). Data were analyzed using 2 two-way ANOVA and Tukey's post hoc test (α=0.05). The mean %SMHC (±SD) amounted to: P (TiF4 - 73.32 ± 5.16 and control - 83.49 ± 4.59) and d (TiF4 - 83.01 ± 7.41 and control - 75.75 ± 2.57). In conclusion, the application of 4% TiF4 solution reduced the softening of permanent enamel but not of deciduous enamel significantly. However, no significant differences were detected between the permanent and deciduous enamel when the factor substrate was considered.
Keywords: Dental erosion; Enamel; Fluoride; Titanium tetrafluoride